Scholen zonder kerk: De impact van ontkerkelijking op open protestants-christelijk basisonderwijs - Miedema, Siebren; Bertram-Troost, Gerdien; ter Avest, Ina; Kom, Cees; de Wolff, Anneke (Religie & Samenleving, 2013)
In this article we deal with the impact of the declining number of church members on so-called open Protestant primary schools in the Netherlands. Such schools are characterized by an open admittance policy in respect to pupils from different religious or worldview backgrounds as long as their parents respect the particular identity of the schools. Besides, a growing number of teachers are no longer church members themselves although they are still believers in the Christian tradition. Our first research question is how these schools deal with the religious identity dimension in this particular and new situation. Our second question is why parents who are not church members and not even Christians still prefer to send their children to open Protestant schools. We will answer these two questions based on the results of two empirical research projects.